(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background. Nationwide lockdowns, encompassing mass quarantine under stay-at-home ordinances, have already proven effective in controlling the COVID-19 outbreak. A prolonged homestay may also be associated with potential side effects, which may jeopardize people’s health. Some undesirable consequences of prolonged homestay can be physical inactivity, behavioral addiction disorders and social isolation (Henry, Bovo, & Sanchis-Gomar, 2020). The aim of the study is to analyse the impact of COVID-19 on mental health and lifestyle in the population of Kaunas city. Methods of research. anonymous online survey, which included questions on demographics, eating habits, alcohol and tobacco consumption, physical activity (Global Physical Activity Questionnaire), sleep quality (Pittsburgh sleep quality index) and mental health (Patient Health Questionnaire – 9). Results. the study involved 388 respondents from Kaunas city. Women accounted for 80,7 %, and men for 19,3 % of respondents. Average of sedentary behavior during the pandemic – 430, 93 ± 233,47 min., before the pandemic – 324, 42 ± 216,21 min. (p <0,05). Average of moderate-intensity physical activity (PA) before the pandemic 122,40 ± 148,98 min., and during the pandemic – 85,33 ± 98,08 min. (p<0,05). Average of vigorous-intensity PA during the pandemic – 21,20 ± 34,13 min, and before – 47,13 ± 104,08 (p<0,05). The consumption of fast food on daily basis before the pandemic – 0,8 %, during the pandemic – 1,5 % (p<0,05). Before the pandemic 15,7 % of respondents overate, during the pandemic – 30,2 % of respondents (p<0,05). Before the pandemic 1,8% of respondents consumed alcohol every day, during the pandemic – 3,4 % of respondents (p<0,05). Symptoms of depression: 7,26 ± 1,46 points before the pandemic and 10,40 ± 2,20 points during the pandemic (p<0,05). Quality of sleep: 5,73 ± 2,20 points before the pandemic and 6,44 ± 2,99 during the pandemic (p<0,05). Conclusion. Sedentary behavior increased, while moderate-intensity and vigorous-intensity PA decreased (p<0,05) during the pandemic. The consumption of fruit and fast food increased during the pandemic (p<0,05) as well as the daily consumption of alcohol (p<0,05). The symptoms of depression were evaluated as mild (5–9 points) before the pandemic, and as moderate (10-14 points) during the pandemic (p<0,05). The quality of sleep was evaluated as worse during the pandemic than before the pandemic (p<0,05). Keywords: COVID-19, lifestyle, mental health, population of Kaunas city.